Labor Shortages in the Florida Strawberry Industry - Zhengfei Guan (EDIS)
The Florida strawberry industry has been plagued by severe labor shortages. This paper investigates growers’ labor demand and labor shortages based on a survey conducted in 2016. We found that labor shortages increase over the season, ranging from a shortage of 14 workers per 100 acres in September to 35 workers per 100 acres in March, the peak harvesting season.